1995
DOI: 10.1002/1520-6629(199501)23:1<3::aid-jcop2290230102>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability and specificity of the stigma associated with the mental illness label: A reconsideration twenty-five years later

Abstract: The current status of the generalizability (i.e., application across situations) and specificity (i.e., differentiation from other deviant behavior stigmas) of the mental illness stigma was re‐examined 25 years after delineation by Lamy (1966). College undergraduate students completed 30 forced‐choice items measuring deep‐level attitudes toward ex‐mental patients vis‐à‐vis ex‐convicts or ex‐drug addicts. Etiological factors and various areas of functioning (i.e., psychological and social functioning, dating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
2
19
0
1
Order By: Relevance
“…In this study, we were concerned with the potentially stigmatizing impact of diagnosis. The stigma of mental illness has long been recognized as a significant social issue (Goodyear & Parish, ) and it has been suggested that diagnostic labels can contribute to this stigmatization process (Skinner, Berry, Griffith, & Byers, ). Further, diagnostic labels can have a devastating effect on an individual's sense of self through a process of internalized stigma where the individual applies negative public perceptions of mental illness to themselves.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we were concerned with the potentially stigmatizing impact of diagnosis. The stigma of mental illness has long been recognized as a significant social issue (Goodyear & Parish, ) and it has been suggested that diagnostic labels can contribute to this stigmatization process (Skinner, Berry, Griffith, & Byers, ). Further, diagnostic labels can have a devastating effect on an individual's sense of self through a process of internalized stigma where the individual applies negative public perceptions of mental illness to themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Corrigan and Penn (1999) have defined stigma as a negative and erroneous attitude about a person, akin to a prejudice or negative stereotype. Public stigma reflects the negative attitudes that the general public has toward people with mental illness, inviting discrimination, fear, and pessimism (Link, 1987;Link, Cullen, Frank, & Wozniak, 1987;Purvis, Brandt, Rouse, Vera, & Range, 1988;Skinner, Berry, Griffith, & Byers, 1995). Self stigma is the internalization of how the general public portrays people with mental illness, and the belief in that portrayal (Corrigan & Watson, 2002;Link, Cullen, Struening, Shrout, & Dohrenwend, 1989;).…”
mentioning
confidence: 99%
“…11 Case presentations containing only the description ex-mental patient, with no symptomatic or behavioral descriptions, results in stigmatization (e.g., Skinner et al). 12 The term schizophrenia is a composite word derived from the Greek words split and mind. This terminology is stigmatizing but the Japanese label may be even more so: seishinbunretsu-byou, a composite of Chinese characters meaning split spirit (or soul) disease.…”
Section: Introductionmentioning
confidence: 99%